Agile organization development model of secondary schools under the office of basic education commission - Kriangkraiwong, Nattaphong; Prasertcharoensuk, Thanomwan; Kanjug, Parnpitcha (Edelweiss Applied Science and Technology, 2025)
The research employed a mixed-methods approach conducted in three phases: (1) document and literature analysis coupled with in-depth interviews with experts; (2) Confirmatory Factor Analysis (CFA) to identify key components; and (3) model development and evaluation. Phase three involved a case study of two prototype schools, the drafting of a Multi-Attribute Consensus Reaching (MACR) model, and its subsequent evaluation for suitability, feasibility, and utility. In Phase 1, a comprehensive literature review and expert interviews established the key components and indicators. Phase 2 employed confirmatory factor analysis on data from 420 administrators and teachers—yielding χ² = 98.479, df = 86 (χ²/df = 1.145), p = 0.1678, RMSEA = 0.020, SRMR = 0.029, CFI = 0.998, and TLI = 0.995—to confirm model consistency. Phase 3 involved developing and evaluating an agile organization model, which comprises a model name, principles and concepts, objectives, 36 practical guidelines, 20 success goals, and 20 mechanisms for driving success. Expert evaluations indicated that the model is highly suitable, feasible, and useful.